Relationship Between Pregnancy Complications and Serum Pregnancy Associated-Plasma-Protein-A and Free-β-Human Chorionic Gonadotropin in the First Trimester Among Iranian Women - Hatav Ghasemi Tehrani; Arezoo Sadeghian; Reza Entezari (Tehran University of Medical Sciences, 2018)
Objective: To evaluate the relationship between maternal serum levels of pregnancy-associated-plasma-protein-A (PAPP-A) and β-human-chorionic-gonadotropin (β-hCG) and pregnancy complications. Materials and methods: This is a case-control study conducted during 2015- 2016. Women at their first pregnancy were enrolled and serum PAPP-A and free-β-hCG were measured in 9-14 weeks of gestation. They were followed till the end of pregnancylooking for complications including preterm labor, pregnancy induced hypertension (PIH), abortion, and intra-uterine growth retardation (IUGR). Results: A total of 1070 pregnant women (mean age: 28.64 ± 4.95 years) were enrolled. Low serum levels of PAPP-A were more frequent in patients developing IUGR (17.4% versus 1.2%, p < 0.001), preterm labor (13% versus 2%, p = 0.013), and PIH (17.4% versus 4%, p = 0.015) compared those without complications. The serum levels of free-β-hCG were not different in patients with and without complications (p > 0.05). Conclusion: There is an association between low serum levels of PAPP-A and developing IUGR, preterm labor, and PIH.